2023
DOI: 10.1038/s41598-023-32676-4
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical settlement behaviours of coral larvae to common coralline algae

Abstract: Natural regeneration of degraded reefs relies on the recruitment of larvae to restore populations. Intervention strategies are being developed to enhance this process through aquaculture production of coral larvae and their deployment as spat. Larval settlement relies on cues associated with crustose coralline algae (CCA) that are known to induce attachment and metamorphosis. To understand processes underpinning recruitment, we tested larval settlement responses of 15 coral species, to 15 species of CCA from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…This result was somewhat surprising because CCA is known to be a strong settlement inducers in Acropora 28 , 31 34 , 86 , 89 . However, Abdul Wahab et al 33 recently demonstrated species-specific preferences amongst a broad taxonomic cross-section of coral/CCA pairings, and Porolithon was not the most universal CCA cue, corroborating previous findings 28 , 30 , 90 , 91 . Therefore, other CCAs may be as effective as rubble at inducing settlement across Acropora spp.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This result was somewhat surprising because CCA is known to be a strong settlement inducers in Acropora 28 , 31 34 , 86 , 89 . However, Abdul Wahab et al 33 recently demonstrated species-specific preferences amongst a broad taxonomic cross-section of coral/CCA pairings, and Porolithon was not the most universal CCA cue, corroborating previous findings 28 , 30 , 90 , 91 . Therefore, other CCAs may be as effective as rubble at inducing settlement across Acropora spp.…”
Section: Discussionsupporting
confidence: 80%
“…It is also likely that biofilm discs supported early successional species (+4 weeks conditioned) 83 that were less mature and inductive than those on rubble fragments. Thirdly, while rubble was visually searched for CCA, it is likely that at least some fragments harboured cryptic and/or recruit CCA communities, which would be more diverse than the single CCA treatment tested and could be highly inductive 31 33 , 86 . As in Turnlund et al 84 , sequencing the cryptic taxa on more and less inductive fragments may provide further insights into key inductive and inhibitory communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperatures, suspended particulate matter, and dissolved inorganic nutrients can inhibit fertilization, fecundity, and larval settlement of coral ( Fabricius, 2005 ; Haas et al, 2016 ). CCA, which contribute to building and solidifying the reef structure ( Lewis, Kennedy & Diaz-Pulido, 2017 ; Weiss & Martindale, 2017 ; Chen et al, 2020 ) and offer settlement cues for coral larvae ( Whitman et al, 2020 ; Deinhart, Mills & Schils, 2022 ; Abdul Wahab et al, 2023 ), have been found to be sensitive to thermal stress ( Webster et al, 2011 ; Vásquez-Elizondo & Enríquez, 2016 ). A positive correlation was observed between increased CCA fragments and an increase in species, type, and coverage of hard corals ( Weiss & Martindale, 2017 ; Whitman et al, 2020 ; Abdul Wahab et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCA, which contribute to building and solidifying the reef structure ( Lewis, Kennedy & Diaz-Pulido, 2017 ; Weiss & Martindale, 2017 ; Chen et al, 2020 ) and offer settlement cues for coral larvae ( Whitman et al, 2020 ; Deinhart, Mills & Schils, 2022 ; Abdul Wahab et al, 2023 ), have been found to be sensitive to thermal stress ( Webster et al, 2011 ; Vásquez-Elizondo & Enríquez, 2016 ). A positive correlation was observed between increased CCA fragments and an increase in species, type, and coverage of hard corals ( Weiss & Martindale, 2017 ; Whitman et al, 2020 ; Abdul Wahab et al, 2023 ). This suggests that an increased availability of CCA in the ecosystem likely increases the diversity and coverage of hard corals.…”
Section: Discussionmentioning
confidence: 99%